Impact of Transformational Leadership on Organizational Culture in Elementary Schools of Lahore - Ali, Areeba Haider; Zaman, Muhammad Shokat; Hassan, Muhammad (Journal of Development and Social Sciences, 2024)
The study investigated the impact of the Principals’ Transformational Leadership (TFL) on the Organizational Culture (OC) in elementary schools at Lahore. For this purpose, a representative sample comprising 171 from various elementary schools in Lahore was selected conveniently. The data were collected with Transformational Leadership Survey (TLS) and the Denison Organizational Survey (DOCS). The collected data were analyzed with the help of Descriptive statistics, Pearson’s r and Regression analysis. Based on the results, it has been concluded that the participants of the study had a positive perceptions regarding Transformational Leadership (TFL) in elementary schools at Lahore and the Organizational Culture (OC). A positive and significant impact of Transformational Leadership (TFL) in elementary schools at Lahore also has been found on the Organizational Culture (OC). It has been recommended that the training should be provided to the school leaders for becoming and practicing the Transformational Leadership.